Who are the users of a traditional Chinese sanfu acupoint herbal patching therapy in China?: A cross-sectional survey. Issue 49 (December 2016) - Zhou, Fen; Wu, Hong-jun; Zhai, Jun-ping; Zhang, Gui-yan; Shao, Yan; Tian, Xia; Xia, Ru-yu; Jia, Li-yan; Li, Wen-yuan; Liang, Ning; Yan, Xiao-yi; Wu, Ruo-han; et al.
Abstract : Abstract: Sanfu acupoint herbal patching (SAHP) is a unique traditional Chinese medicine therapy, which has become popular for preventing acute attack of respiratory diseases such as asthma and chronic obstructive pulmonary disease, in many regions of mainland China. However, the knowledge about its users is lacking, especially the characteristics of the users and their experience and perspectives. To investigate the demographics of users, conditions for its use and the previous experience of SAHP, as well as users' perspectives to provide baseline information for its practice. A cross-sectional consecutive-sample survey was conducted at outpatient departments from 3 traditional Chinese medicine hospitals in northern China. Each participant completed a questionnaire, after informed consent. Data description and analyses were done using SPSS 20.0. Among 949 SAHP users from 3 hospitals, female was predominant (n = 592; 62.4%), aged from 2 to 96 years (median = 52 years). 64.7% (380/587) of regular users have applied consecutively for 3 years or over, and the self-perceived satisfaction rates of respiratory diseases were from 45.9% to 77.7%. Positive attitude toward traditional Chinese medicine was the top reason for choosing SAHP. 42.4% of users held a motivation of being cured by SAHP and with great outcome expectancy on SAHP (70.8%). SAHP users were mainly female adults or elderly population; more than half were regular users, who predominantly used SAHP for various chronic respiratory diseases during their stable stage. The majority of users expressed satisfaction to previous SAHP for their respiratory diseases. 42.4% of users held a motivation of being cured by SAHP and with great outcome expectancy on SAHP (70.8%). The findings from this survey deserve further clinical trials for their clinical effectiveness.